Effects of Saline Irrigation of the Bile Duct to Reduce the Rate of Residual Common Bile Duct Stones: A Multicenter, Prospective, Randomized Study. (April 2018) - Ahn, Dong‐Won; Lee, Sang Hyub; Paik, Woo Hyun; Song, Byeong Jun; Park, Jin Myung; Kim, Jaihwan; Jeong, Ji Bong; Hwang, Jin‐Hyeok; Ryu, Ji Kon; Kim, Yong‐Tae
Abstract : OBJECTIVES: In clinical practice, recurrent cholangitis due to residual common bile duct (CBD) stone occurs frequently even after endoscopic stone removal. This study aimed to determine whether preventive saline irrigation of the bile duct (PSIB) after endoscopic removal of CBD stones would decrease the residual CBD stones. METHODS: In this multicenter, prospective, randomized study, patients who received endoscopic retrograde cholangiopancreatography for removal of CBD stone were randomized to either receiving PSIB after stone removal (PSIB group) or not receiving PSIB (non‐PSIB group). Patients were prospectively followed up and the presence of residual CBD stones was evaluated within 6 months after endoscopic stone removal. RESULTS: A total of 148 patients were enrolled and completed follow‐up (73 in PSIB group and 75 in non‐PSIB group). The two groups were similar with regard to baseline characteristics. Residual CBD stones were detected in 22 patients (14.9%). The incidences of residual CBD stones were 6.8% in PSIB group and 22.7% in non‐PSIB group ( P =0.010). Multivariate analysis revealed that the performance of PSIB and the presence of only a single‐CBD stone were the significant factors for the decrease of the occurrence of the residual CBD stones. Although, procedure time was slightly longer in PSIB group (22.0 vs 19.2 min, P =0.037), no significant difference was observed in the procedure‐related complications between the two groups. CONCLUSIONS: PSIB could reduce the residual CBD stones without increasing complications. Considering the efficacy and safety, routine PSIB after endoscopic CBD stone removal seems to be preferred (ClinicalTrials.gov identifier: NCT01425177).